Analysis of education problems at higher education institutions - Korsakienė, Renata (Business: Theory and Practice, 2006)
The Bologna declaration stresses the importance of education and educational co-operation in the development and strengthening of stable, peaceful and democratic societies. Additionally the declaration highlights the need to promote European co-operation in quality assurance with a view to develop comparable criteria and methodologies. The cooperative activity of universities created preconditions for students’ mobility under the Leonardo da Vinci and Socrates programmes. Hence, a comparison of efficiency of engineering education studies at partner institutions has become a topical issue. The paper presents the problems related to engineering education quality at different universities and suggests a system of indicators that are applicable for education quality estimation. The main idea is to compare the distinguished aspects of the education process and to evaluate quality of teaching. The efficiency of different subjects (social and engineering) is estimated by applying sets of criteria, to be implemented by incorporating a proposed system of criteria into questionnaires for students at Vilnius Gediminas Technical University (VGTU), who participate in student mobility programmes. Processing of the received responses let the author achieve the ultimate aim, i.e. to trace differences in the quality of teaching. Policy implications in the field of engineering education quality management are seen as main outcome of presented research.